Benchmarking as an instrument for improvement of quality management in higher education - Paliulis, Narimantas Kazimieras; Labanauskis, Rimvydas (Business, Management and Economics Engineering, 2015)
Conditioned by globalisation and constant change, higher education institutions (HEIs) are forced to pursue new instruments for quality assurance in higher education. States seem to pursue this aim by attempting to create an efficiently operating system of higher education that satisfies needs of diverse societal groups. Quality dimension is the most important element of efficient and effective higher education. From the perspective of a state, assessment and monitoring of quality are instruments for the management of processes of higher education. The article substantiates these statements using the evolution of the dimension of quality in the European and Lithuanian higher education in the course of the Bologna Process. The article also presents a benchmarking method and discusses its development and application tendencies in business organisations. Also, it looks at possibilities to apply this method in higher education. The main aim of this article is to explore benchmarking as an effective instrument for the improvement of performance quality in HEIs and complement the already implemented quality management systems. Another aim is to suggest this method to national agencies for quality assurance in higher education for monitoring and analysis of qualitative changes on the systematic level. The object of the article is the improvement of performance quality in HEIs. Benchmarking is proposed for the use in higher education on the institutional level as an instrument that complements presently introduced quality management systems in Lithuanian HEIs. This way, it will contribute to the formation of the culture of quality in higher education.